Architecture for the Secret-Key BC3 Cryptography Algorithm - Arif Sasongko; Hidayat Hidayat; Yusuf Kurniawan; Sarwono Sutikno (Journal of ICT Research and Applications, 2011)
Cryptography is a very important aspect in data security. The focus of research in this field is shifting from merely security aspect to consider as well the  implementation  aspect.  This  paper  aims  to  introduce  BC3  algorithm  with focus  on  its  hardware  implementation.  It  proposes  an  architecture  for  the hardware  implementation  for  this  algorithm.  BC3  algorithm  is  a  secret-key cryptography  algorithm  developed  with  two  considerations:  robustness  and implementation  efficiency.  This  algorithm  has  been  implemented  on  software and has good performance compared to AES algorithm. BC3 is improvement of BC2 and AE cryptographic algorithm and it is expected to have the same level of robustness and to gain competitive advantages in the implementation aspect. The development of the architecture gives much attention on (1) resource sharing and (2)  having  single  clock  for  each  round.  It  exploits  regularity  of  the  algorithm. This architecture is then implemented on an FPGA. This implementation is three times smaller area than AES, but about five times faster. Furthermore, this BC3 hardware  implementation  has  better  performance  compared  to  BC3  software both in key expansion stage and randomizing stage. For the future, the security of this implementation must be reviewed especially against side channel attack.